Issues at the Rural-Urban Fringe: Will Florida Be Prepared for 2030? - Rodney L. Clouser (EDIS)
U.S. Census Bureau population projections estimate Florida's 2030 population will be almost 29 million residents. FE661, a 9-page fact sheet by Rodney L. Clouser, identifies some of the policy issues which are most important for the state to address, and encourages policy-makers to start addressing those issues now before they become more troublesome and the solutions become more limited. Includes references. Published by the UF Department of Food and Resource Economics, August 2006.